Intrinsic Factors Influencing Career Choice of Music Graduates in Fujian, China - Xiaolu Wang; Chiew Hwa Poon; Ku Wing Cheong (MDPI AG, 2024)
Career choice has received significant attention in recent years, with research indicating a strong correlation between individual intrinsic motivations and career decisions. This study investigated the intrinsic factors influencing music graduates' decisions to pursue a professional career in music in Fujian, China, using the Exploratory Design research method. This research design involved two phases. In phase one, the influencing factors were explored through interviews seeking to obtain qualitative information (N = 18). In phase two, the codes derived from the qualitative study were utilized to build a Likert scale for the quantitative questionnaire (N = 221). The qualitative results revealed that music graduates' professional career choices were intrinsically influenced by their commitment to the music profession, sense of self-worth derived from successful performing and teaching experiences, self-purpose in sharing and teaching music, interest in music playing and music teaching, confidence in music-playing skills, and working relationship between teacher and student. These variables were confirmed by the quantitative study to have an impact on career choice. Commitment to the music profession was the most influential variable, followed by a sense of self-worth. Confidence in music-playing skills was the least influential variable. These findings deepen our understanding of the variables impacting music majors' job choices. Understanding these determinants can help educational institutions, policymakers, and career counselors better understand music majors' particular needs and concerns, leading to more supportive career pathways for aspiring musicians in the region.